2022
DOI: 10.3390/jcm11195506
|View full text |Cite
|
Sign up to set email alerts
|

The Etiology of Community-Acquired Pneumonia Correlates with Serum Inflammatory Markers in Children

Abstract: Community-acquired pneumonia (CAP) severely affects pediatric hospitalizations. This study assessed the contribution of CAP to hospitalizations, its etiology in relationship with age, and the inflammatory markers. Between 2013 and 2018, 1064 CAP patients were hospitalized and diagnosed with bacterial/possibly bacterial pneumonia (BP), viral/possibly viral pneumonia (VP) and atypical pneumonia (AP). The etiology was confirmed using blood/pleural fluid culture/polymerase chain reaction (PCR), rapid antigen test/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…We did not find any studies that evaluated presepsin levels in children with RTIs. The full list of studies included in this scoping review is detailed in tables, and the Excel form for all details assessed for each study is available upon request to the corresponding authors [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…We did not find any studies that evaluated presepsin levels in children with RTIs. The full list of studies included in this scoping review is detailed in tables, and the Excel form for all details assessed for each study is available upon request to the corresponding authors [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that blood inflammatory biomarkers, such as procalcitonin and CRP, can assist in differentiating between bacterial and viral CAP ( 28 , 29 ). In recent years, platelets have been found to detect endothelial cell damage and pathogenic microorganism invasion, forming the first line of defense against pathogenic infections ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many approaches to differentiate viral and bacterial CAP have been studied without definitive conclusions (consolidation on chest radiograph, inflammatory markers, induced sputum, etc.) [4][5][6]. Viruses (>70%) are by far the most common identified pathogen in hospitalized children with CAP, followed by Mycoplasma pneumoniae (8%) and Streptococcus pneumoniae (4%) [7].…”
Section: Epidemiologymentioning
confidence: 99%